A efetividade dos princípios constitucionais do contraditório e da ampla defesa no inquérito civil - Jorge, André Guilherme Lemos (2007)
The objective of the following essay is to demonstrate how the constitutional principles of the rights to contest and of legal defense should be applied to the acts within the public prosecution. This kind of process is based in inquiring examination, which requires secrecy. To support the adversary practice here would, therefore, be an incongruent statement. After studying the evolution of the study of legal principles, we traced an epistemological division, to present the value and the reach of the laws constitutionally originated as fundamental rights. Now, appears the conflict between national security, represented by the secret investigation, against the due process of law, guarantied as an individual liberty. As an immediate consequence of the due process of law, we find the right to contest and the right of legal defense, concluding that the State of Law will only achieve its plenitude when all aspects of legitimate defense become effectively guarantied. Intending to penetrate profoundly within the inquisition instrument, centered as object of this essay; we drove through the roads traced by experts in Public Law, in innumerous attempts to define the series of acts and facts bonded in the heart of the Public Administration. The administrative process is a conquest of conceptual revolution, aroused after many debates, mainly when we determined the exact limits between the State functions. The Public District Attorney Office, once born to cohibit arbitrary acts, originated from the concentration of inquisitor and decision making powers in the hands of the sovereign one, now tends to insert itself in this power concentrating position. One of its most powerful instruments, the public prosecution, attributes to each member of the D.A. Office a compound of immense investigatory powers, a fact that per se, is enough to embrace the present theory. The conclusion arrived, giving prestige to modern public process policies and demanding the effectiveness of constitutional principles, lines itself in a parallel position to the world search for the materialization of human rights